Source Odor, Intensity, and Exposure Pattern Affect Antipredatory Responses in the Subterranean Rodent Ctenomys talarum - Brachetta, Valentina (2016)
Predation is a strong selective force, and prey species may show specific adaptations that allow recognition, avoidance, and defense against predators. Facing a situation of predatory risk, anxiety constitutes a reaction of adaptive value, allowing to evaluate the potential risk of this encounter as well as to generate a physiological and behavioral response. Previous studies in the subterranean rodent Ctenomys talarum revealed that exposure to predator odors (urine or fur) generates an anxiety state and induces behavioral changes. However, no differences between the responses generated by both odor sources were observed, although fur odors may indicate a higher level of predatory immanence. Therefore, the aim of this study was to evaluate the behavioral and physiological responses of C. talarum to different intensities of predator odors (urine and fur) and to the repeated exposition to the same odorous stimulus. When comparing the highest behavioral effects elicited by both predatory odors on C. talarum, our study supports the assumption that fur odors are more anxiogenic than urine, while the former provoked significant changes in the distance traveled, the number of arm entries and time in transparent arms in the elevated plus maze; cat urine only caused slight changes on those behavioral parameters. Furthermore, we also found that the intensity of natural predator odor presented to tuco-tucos has a role on the appearance of defensive behaviors, although an amount-dependent relationship between predator odor and anxiety levels was not observed. Finally, while individuals exposed for 1 day to fur odor displayed an evident anxiety state, those exposed repeatedly for 5 consecutive days did not differ with the control group in their behavioral response, indicating a clear habituation to the predatory cue. In our intensity and habituation experiments, we did not find differences in the measured physiological parameters among control individuals, exposed to different cues intensity (urine and fur odor) and exposed only once or for 5 days to fur odor. These results provide valuable evidence that the types of predatory odor, along with the frequency of exposition, are important determinants of the appearance, strength, and extinction of defensive behaviors in the subterranean rodent C. talarum.